Factors affecting sustainability of mHealth decision support tools and mHealth technologies in Malawi. (2019) - Chirambo, Griphin Baxter; Muula, Adamson S.; Thompson, Matthew
Abstract: Initial roll out of mHealth decision-making tools to support management of acute child illness in Malawi has been positive. However, it is necessary for these programs to be sustainable. The aim of this study was to explore the factors that affect the sustainability of mHealth decision-making tools in Malawi. A qualitative approach was used in this study, and a total of 19 study participants were purposively selected. These included officials in the Ministry of Health, the district health office, non-governmental organizations (NGOs) implementing mHealth, Integrated Management of Childhood Illnesses (IMCI) coordinators and the Health surveillance Assistants (HSAs). A semi-structured interview guide was developed based on the Program Sustainability Assessment Tool (PSAT) framework. Data was analysed manually using a thematic analysis process. We found the following themes that appeared to be most important in affecting the sustainability of using mHealth decision-making tools and mHealth technologies in Malawi. These are environmental support, funding stability, partnerships, organizational capacity, program evaluation and strategic planning. There is good political will from the MoH to continue supporting the mHealth programs. However, there is a need for a robust collaboration with the NGOs involved in the implementation of mHealth technologies. The telecommunications infrastructure was also found to be crucial for the mHealth decision-making program to be sustainable in Malawi. In Malawi, the sustainability of mHealth tools for children under 5 care can depend on a robust level of political commitment from the government through the MoH authorities, working in collaboration with NGOs involved in these technologies. However, dedicated support for the mHealth program itself from the government and other stakeholders is needed, as well as improvements to telecommunications infrastructure, which will be critical for continued deployment.